1979
DOI: 10.1177/000348947908800601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transverse Temporal Bone Fracture on the Fluid Compartment of the Inner Ear

Abstract: Five temporal bones exhibiting transverse fractures were studied with a view to determining whether such fractures could lead to symptomatic endolymphatic hydrops. Four out of the five temporal bones showed the fracture line traversing the vestibular aqueduct. Two of these four showed complete obstruction of the endolymphatic duct. One of these had an intact membranous labyrinth and severe endolymphatic hydrops. The other had ruptures of the membranous labyrinth and no hydrops. Three ears exhibited partial pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…There are limited observations regarding vestibular nerve status and/or counts of ScGCs in the literature. Although Rizvi and Gibbin described moderate‐to‐severe degeneration of neurons in the vestibular nerves in four human TBs following TBF, they did not explain how the specimens were assessed or to what normative data they were compared to. Instead, their analysis of vestibular nerve degeneration appears to be based on qualitative appearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited observations regarding vestibular nerve status and/or counts of ScGCs in the literature. Although Rizvi and Gibbin described moderate‐to‐severe degeneration of neurons in the vestibular nerves in four human TBs following TBF, they did not explain how the specimens were assessed or to what normative data they were compared to. Instead, their analysis of vestibular nerve degeneration appears to be based on qualitative appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Blockage of the ED has been previously reported in other cases with transverse TBFs. Rivzi and Gibbon have described fracture lines traversing the vestibular aqueduct, in which one of three presented with complete obstruction of the ED . The authors proposed that TBFs affecting the vestibular aqueduct could lead to EH and symptoms resembling Ménière's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of hearing loss related to brain injury are as follows: 1) injury to the central auditory pathways, which may result in severe deafness; 2) temporal bone fracture with otic capsule involvement, which may result in three types of hearing loss, including sensorineural hearing loss, conductive hearing loss, and mixed type; 3) tympanic membrane rupture with conductive hearing loss; 4) ossicular chain disruption complicated with conductive hearing loss; 5) cochlear disruption due to barotrauma; 6) anterior and posterior movement of the brain by coup or contracoup injuries, resulting in a shearing injury to the auditory nerve; 7) disruption of the membranous labyrinth; 8) avulsion or trauma to the cochlear nerve; 9) interruption of the cochlear blood supply; 10) hemorrhage into the cochlea; 11) perilymphatic fistula; and 12) endolymphatic hydrops . Griffiths et al reported that the force of a blow to the temporal region is the likeliest and most severe cause of sensorineural hearing loss .…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous human studies indicating that obstruction of the ELD from various means, including vascular anomalies or internal sac disease, may result in EH 10 . Rizvi and Gibbin 11 studied five temporal bones exhibiting transverse fractures, four of which demonstrated fracture lines traversing the VA. One temporal bone with complete obstruction of the ELD had severe hydrops and a clinical presentation of Meniere's disease. EH also has been uniformly identified in temporal bones with otosclerotic disease completely filling the VA 12 .…”
Section: Discussionmentioning
confidence: 99%